Heterogeneous environmental seascape across a biogeographic break influences the thermal physiology and tolerances to ocean acidification in an ecosystem engineer. (28th January 2022) - Rodríguez‐Romero, Araceli; Gaitán‐Espitía, Juan Diego; Opitz, Tania; Lardies, Marco A.
Abstract: Aim: Understanding how spatio‐temporal environmental variability influences stress tolerance, local adaptation and phenotypic variation among populations is a key challenge for evolutionary ecology and climate change biology. Coastal biogeographic breaks are natural laboratories to explore this fundamental research question due to the contrasting environmental conditions experienced by natural populations across these regions. Location: In the South East Pacific (SEP) coast, a major break (30º‐32ºS) is characterized by extreme natural variability in sea surface temperature (SST) and carbonate chemistry parameters related to temporal and spatial dynamics in upwelling events. Calcifying organisms inhibiting this zone are exposed to marked fluctuations and clines in SST that together with naturally acidified waters can impact their metabolism, calcification and fitness, making them particularly prone to the effects of climate change (e.g. ocean acidification, OA). We investigated to what extent the spatial and temporal environmental variability (in SST and seawater carbonate conditions) that characterizes the biogeographic break in the SEP influences intra‐specific differences in the thermal ecology and the tolerances to OA of the limpet Scurria araucana . Methods: During two years, we conducted field surveys of limpet populations at sites across the SEP break (27ºS, 30ºS and 32ºS). We collected individuals from each population to test for geographic differences in morphometric (e.g. total buoyancy weight, shell length) and physiological (e.g. oxygen consumption rate, cardiac activity and thermal performance curves; TPC) responses to local environmental conditions (Tº and pH/pCO2 ) and to simulated OA scenarios. Results: Populations of S . Araucana exhibit high tolerance to OA with no signal of geographic influence on this attribute. However, inter‐population differences in thermal physiology (metabolic rates and performances) were found across the biogeographic break in the SEP coast. Limpets from the central part of the break (30ºS) exhibit higher thermal performance compared to limpets from populations at both sides of the break. Main conclusions: Variation in SST has a greater effect shaping inter‐population differences in thermal physiology of the limpet S . araucana . These physiological differences are aligned the thermal heterogenous seascape along the biogeographic break in the SEP. Contrarily, temporal and spatial variation in seawater carbonate conditions does not influence inter‐population differences in phenotypic response populations, but an overall high tolerance to OA.